Cultivation of parasites - Ahmed, Nishat Hussain (Medknow Publications & Media Pvt Ltd, 2014)
Parasite cultivation techniques constitute a substantial segment of present-day study of parasites, especially of protozoa. Success in establishing in vitro and in vivo culture of parasites not only allows their physiology, behavior and metabolism to be studied dynamically, but also allows the nature of the antigenic molecules in the excretory and secretory products to be vigorously pursued and analyzed. The complex life-cycles of various parasites having different stages and host species requirements, particularly in the case of parasitic helminths, often make parasite cultivation an uphill assignment. Culturing of parasites depends on the combined expertise of all types of microbiological cultures. Different parasites require different cultivation conditions such as nutrients, temperature and even incubation conditions. Cultivation is an important method for diagnosis of many clinically important parasites, for example, Entamoeba histolytica, Trichomonas vaginalis, Leishmania spp., Strongyloides stercoralis and free-living amoebae. Many commercial systems like InPouch TV for T. vaginalis, microaerophilous stationary phase culture for Babesia bovis and Harada-Mori culture technique for larval-stage nematodes have been developed for the rapid diagnosis of the parasitic infections. Cultivation also has immense utility in the production of vaccines, testing vaccine efficacy, and antigen - production for obtaining serological reagents, detection of drug-resistance, screening of potential therapeutic agents and conducting epidemiological studies. Though in vitro cultivation techniques are used more often compared with in vivo techniques, the in vivo techniques are sometimes used for diagnosing some parasitic infections such as trypanosomiasis and toxoplasmosis. Parasite cultivation continues to be a challenging diagnostic option. This review provides an overview of intricacies of parasitic culture and update on popular methods used for cultivating parasites.